PENGEMBANGAN MEDIA ULAR TANGGA DALAM PEMBELAJARAN SEJARAH DIKELAS X SMAN 6 PONTIANAK - Astriadi, Ricky; Usman, Andy; Riva ie, Wanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe use of Snake and Ladder game in history lesson can motivate of senior high school number 6 of grade x to learn history subject as their average score for history subject is still 71. The study aims to describe (1) snake and ladder game in history lesson, (2) profile of snake and ladder game, (3) steps to use the game, (4) students’ effectivity in using game. Using Borg And Gall Concept, this Reseach & development study used procedural descriptive method to explain the game making. The media was prepared by following steps (1) Choosing Material (2) Collecting Materials (3) Writing scripts (4) Making Storyboard (5) Sketch (6) Modifying The Game (7) Inserting Text and Voice (8) Finishing. The result reveals that 3.82 (good) was given by the material expert, 4,7 (very good) was credited by media expert, 4,8 (very good) was for preliminary field test, 4,78 (very good) was for main field test, and 4,7 (very good) was fpr operational field test it is concluded that this teaching media is feasible as an alternative teaching media for history lesson.                                                                                                                                           Keywords: Development, snakes and ladder Media, Learning History